Factors Related to Low COVID-19 Vaccination Rate in Pregnant and Postpartum Women with and without COVID-19 - Dilek Menekse Beser; Derya Uyan Hendem; Deniz Oluklu; Ezgi Turgut; Necati Hancerliogullari; Sule Goncu Ayhan; Ozlem Moraloglu Tekin; Dilek Sahin (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective This study focused on pregnant and postpartum women during the COVID-19 pandemic, aiming to determine the attitudes and behaviors of vaccinated and unvaccinated groups, and the vaccination behaviors in the groups with and without the disease. The reasons for refusing the vaccine were also questioned. Methods This cross-sectional study was performed from September 2021 to October 2021. The study data were collected using a face-to-face questionnaire. The participants were pregnant women who applied to the hospital for routine antenatal care and were hospitalized, and women in the postpartum period. Additionally, pregnant and postpartum patients who were diagnosed with COVID-19 at the time of admission and were hospitalized and admitted to the intensive care unit due to this disease were also included in the study. Results A total of 1,146 pregnant and postpartum women who completed the questionnaire were included in our study. Only 43 (3.8%) of the participants were vaccinated; 154 (13.4%) of the participants had comorbidities. The number of COVID-19-positive patients was 153. The lack of sufficient information about the safety of the COVID-19 vaccine is the most common reason for the refusal. Conclusion Vaccine refusal can significantly delay or hinder herd immunity, resulting in higher morbidity and mortality. Considering the adverse effects of COVID-19 on pregnancy, it is essential to understand pregnant and postpartum women's perceptions toward vaccination to end the pandemic.